2018
DOI: 10.3390/en11071837
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Structure Interaction Modelling of Tidal Turbine Performance and Structural Loads in a Velocity Shear Environment

Abstract: Tidal Current Turbine (TCT) blades are highly flexible and undergo considerable deflection due to fluid interactions. Unlike Computational Fluid Dynamic (CFD) models Fluid Structure Interaction (FSI) models are able to model this hydroelastic behavior. In this work a coupled modular FSI approach was adopted to develop an FSI model for the performance evaluation and structural load characterization of a TCT under uniform and profiled flow. Results indicate that for a uniform flow case the FSI model predicted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Bahaj et al considered the influence of the support on MCT performance and placed it as far as at least one rotor radius downstream of the rotor. The variation would be larger a velocity profile of 1/7th power law was used instead of uniform velocity [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahaj et al considered the influence of the support on MCT performance and placed it as far as at least one rotor radius downstream of the rotor. The variation would be larger a velocity profile of 1/7th power law was used instead of uniform velocity [22].…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is beneficial to consider the interaction between the structure and the flow field in evaluating the performance and the details of the structure response of MCTs. Badshah et al [22] compared the one-way and two-way FSI method applied to an MCT modeled as a structural-steel solid. The maximum blade displacement was only 1/2000 of its radius.…”
Section: Introductionmentioning
confidence: 99%
“…While velocity profiles vary considerably from site to site depending on the local bathymetric conditions, these velocity profiles can typically be approximated using power laws. The 1/7th and 1/10th power laws have been used to estimate the velocity profiles for EPRI North American tidal in stream power feasibility demonstration project [40] and other previous research works [14,38]. The flow is assumed to only vary along the depth, and stays uniform across the width of the domain.…”
Section: Simulation Conditions and Load Parametersmentioning
confidence: 99%
“…However, the focus of the study was solely on the hydrodynamic performance of the turbine under the effect of wave-current interaction. We developed a similar full 3D FSI analysis methodology requiring a shorter computational time for a small scale tidal turbine rotor [38]. While our study reported the load variation during a rotation cycle, the turbine design was a scale model, the support structure/tower was not included, and the blade design was simplified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation